Clinical importance of Bcl-2-like 11 deletion polymorphism in idiopathic pulmonary fibrosis - Isobe, Kazutoshi; Issiki, Takuma; Sakamoto, Susumu; Sano, Go; Takai, Yujiro; Tochigi, Naobumi; Homma, Sakae (Journal of Thoracic Disease, 2019)
Background: Reactive oxygen species (ROS) can play a role in the pathogenesis of Idiopathic Pulmonary Fibrosis (IPF) by contributing to epithelial damage. Bcl-2-like 11 (BIM) is involved in the generation of ROS via forkhead box O3 (FOXO3), and a BIM deletion polymorphism related to apoptosis has been reported to be specific to Asians. Here we examine the clinical features of IPF in patients with BIM deletion polymorphism. Methods: In this single-center retrospective study, we reviewed the medical records of 63 patients with IPF who were treated at our hospital from January 2006 through April 2018. Patients with and without BIM deletion polymorphism were compared in relation to clinical characteristics, pulmonary function test results, frequency of acute exacerbation (AE)-IPF, and redox status [including oxidized glutathione (GSSG), reduced glutathione (GSH), 8-hydroxy-2'-deoxyguanosine (8-OHdG), and 8-isoprostane (8-iso)] at baseline and at 1 and 2 years after treatment. Results: No fatal AE-IPF occurred in patients with BIM deletion polymorphism (0% vs. 36.4% of polymorphism-negative cases; P=0.038). Change in forced vital capacity from baseline (ΔFVC) at 2 years was significantly lower in patients with the BIM deletion polymorphism than in those without the polymorphism (‒0.42±0.50 vs. ‒0.88±0.83 L, respectively; P=0.045). Total blood glutathione (tGSH) was significantly higher in patients with the deletion polymorphism than in those without the polymorphism (988±48.3 vs. 858±25.8 µM, respectively; P=0.042). 8-iso was significantly lower in the former group (246.1±81.6 vs. 400.9±334.1 pg/mL, respectively; P=0.022). Conclusions: IPF patients with BIM deletion polymorphism had a good redox balance and may thus have a better clinical outcome than patients without this polymorphism.